Impact of a family dental nursing care home visit model on dental behavior and dental health status in Banda Aceh City, Indonesia - Reca, Reca; Sofyan, Hizir; Andriany, Poppy; Marthoenis, Marthoenis (International Journal of Innovative Research and Scientific Studies, 2025)
Dental health is an important part of overall health. Many individuals still face challenges in maintaining their oral health. In Indonesia, the prevalence of dental diseases including dental caries and gingivitis remains relatively high, particularly in underserved areas like Banda Aceh City. This study evaluates the impact of the family dental nursing care home visit model on dental behavior and health status in the Baiturrahman District of Banda Aceh City. The research divided participants into intervention and control groups using a quasi-experimental design with pre- and post-test control groups. The findings demonstrated the effectiveness of the home visit model conducted in the Baiturrahman sub-district. Significant improvements were noted in various aspects of oral health. The knowledge of oral health among participants increased by an average of 5.639 ± 3.204 points. Attitudes toward dental care improved as well with an increase of 5.115 ± 4.673 points. Practical dental hygiene behaviors also saw a notable enhancement with a rise of 5.902 ± 2.942 points. Additionally, there was a significant reduction in the oral hygiene index by 2.4672 ± 0.9919 and the plaque index decreased by 21.492 ± 12.793. The prevalence of gingivitis dropped by 1.2541 ± 0.7133 indicating better gum health alongside an overall improvement in dental caries status. These results suggest that family dental nursing care through home visits serves as an effective and constructive model for enhancing dental health behaviors.